The Model Regulation of Know Your Customer Principles in Technology-Based Lending and Borrowing in Indonesia - Putri Purbasari Raharningtyas Marditia; Ridani Faulika (JURNAL AKTA, 2022)
The Financial Services Authority Regulation Number 77 /POJK.01/2016 concerning Information Technology-Based Lending and Borrowing Services does not provide details on the process of applying the know-your-customer principle. AsÂ  Article 42 of the Financial Services Authority Regulation Number 77 /POJK.01/2016 only states that organizers are required to implement anti-money laundering and terrorism financing prevention programs in the financial services sector. Cases on users who can use many online loan applications (pinjol) unfairly, proves that there are loan companies disregarding the background, eligibility and ability of the borrower or known as credit scoring, which is the method used by a financing institution/bank in determining whether or not it is appropriate to receive a loan from the institution. Currently, the Financial Services Authority (OJK) itself has prepared a Draft OJK Circular Letter (RSEOJK) on Guidelines for the Implementation of Anti-Money Laundering and Prevention of Terrorism Financing Programs for Information Technology-Based Borrowing-Lending Service Providers which can be used as a basis for implementing KYC p2p lending activities in Indonesia. This research is conducted based on the above, the writing method is a normative juridical method with a statutory and conceptual approach. The purpose of this study is to provide an overview and analysis related to the implementation of KYC consisting of Customer Due Diligence (CDD) and Enhanced Due Diligence (EDD), which may provide better protection than previous regulations. Based on this, the writer is interested in doing this research